Real-time patterns of smoking and alcohol use: an observational study protocol of risky-drinking smokers. Issue 1 (6th January 2015) - Cohn, Amy; Brandon, Thomas; Armeli, Stephen; Ehlke, Sarah; Bowers, Molly
Abstract : Introduction: Despite the strong relationship between smoking and health-related consequences, very few smokers quit. Heavy drinking is a significant risk factor for health consequences, and is implicated in persistent smoking and less success at quitting smoking. Self-efficacy (SE) to abstain from smoking is an important determinant of smoking outcomes and may link alcohol use to poor quit rates. Even though research has demonstrated a strong association between drinking and smoking, and the multiplicative effect of these substances on cancer-related, heavy-drinking smokers has been largely ignored in the literature. Further, research has not taken advantage of innovative methods, such as ecological momentary assessment, to capture the impact of daily factors on smoking cessation outcomes in this particular group. The proposed study identifies daily changing factors that impede or promote SE and future smoking cessation efforts in risky-drinking smokers. Methods and analysis: This is an observational study of 84 regular smokers (≥10 cigarettes per day) who drink at risky levels, report a desire to quit in the next 6 months, and show no evidence of psychiatric disturbance, severe history of alcohol withdrawal or drug dependence (excluding nicotine and caffeine). Participants report on their smoking, alcohol consumption and SE related to smoking twice a day for 28 days using interactive voice response (IVR) surveys. Multilevel regression and path models will examine within-person daily associations among drinking, smoking and SE, and how these variables predict the likelihood of future smoking behaviour at 1 and 6 months follow-up. Ethics and dissemination: This protocol was approved by an accredited Institutional Review Board. The findings will help us understand the factors that promote or impede smoking cessation among a high-risk group of smokers (heavy-drinking smokers) and will be disseminated through peer-reviewed journal articles and presentations at national conferences.